Postpneumonectomy syndrome in a newborn after esophageal atresia repair. (2015) - Iacusso, Chiara; Bagolan, Pietro; Bottero, Sergio; Conforti, Andrea; Morini, Francesco
Highlights: After esophageal atresia repair, if postpneumonectomy syndrome develops, an associated esophageal lung must be considered. Contrast esophagography, with the patient lying on the side of collapsed lung, is the optimal diagnostic study. In infants with postpneumonectomy syndrome, infusion of normal saline in the hemithorax on the side of collapsed lung is a simple, rapid, and effective method to obtain mediastinum realignment in emergency with immediate improvement of clinical conditions. Abstract: Introduction: Postpneumonectomy syndrome (PPS) is an ominous complication, caused by mediastinal shift following massive lung resection. Presentation of the case: A neonate with oesophageal atresia and tracheo-oesophageal fistula developed acute respiratory distress shortly after surgery, despite mechanical ventilation. The patient was found to have an associated oesophageal right lung that collapsed after oesophageal atresia repair and a left pulmonary artery sling causing left main bronchus stenosis mimicking a postpneumonectomy syndrome. Discussion: We will describe the diagnostic work-up and the therapeutic measures used both in the acute phase and as definitive treatment in this challenging case. Conclusions: Neonatologists and paediatric surgeons should be aware of this rare association that may cause acute life threatening and worsening of patient's clinical status. Prompt realignment of the mediastinum in the normal position is critical to obtain rapid improvement of the patient's clinical conditions.